Iron overload despite partial gastrectomy. Issue 648 (October 1979) - Parfrey, P. S.; Turnbull, A. L.; Pollock, D. J.; Barnett, M.
Abstract : Iron overload was found in 3 patients who had undergone partial gastrectomy: a 61-year-old woman developed iron overload because she may have had idiopathic haemochromatosis and had also been given parenteral iron; in a 62-year-old man with thalassaemia minor, iron overload may have developed because of increased oral iron ingestion, low serum folate, increased, albeit ineffective, erythropoiesis and sideroblastic anaemia; a 74-year-old man with thalassaemia minor developed iron overload without exogenous therapy and died from a hepatoma. These cases illustrate that partial gastrectomy fails to protect patients from developing iron overload, particularly if given uncontrolled iron therapy.